Cancer Treatment With the Ketogenic Diet: A Systematic Review and Meta-analysis of Animal Studies - Li, Jing; Zhang, Haiyan; Dai, Zhu (Frontiers in Nutrition, 2021)
Background: The ketogenic diet (KD) has been reported to play an important role in the development of cancer by an abundance of preclinical experiments; however, their conclusions have been controversial. We therefore aimed to perform a systematic review and meta-analysis of animal studies evaluating the effects of KD on cancer. Methods: Relevant studies were collected by searching PubMed, Embase, and Web of Science. Outcome measures comprised tumor weight, tumor volume, and survival time. Meta-analysis was performed using the random-effect model according to heterogeneity. Results: The search resulted in 1,254 references, of which 38 were included in the review and 17 included in the meta-analysis. Pooled results indicated that KD supplementation significantly prolonged survival time [standardized mean difference (SMD) = 1.76, 95% CI (0.58, 2.94), p = 0.003], and reduced tumor weight [SMD = -2.459, 95% CI (-4.188, -0.730), p = 0.027] and tumor volume [SMD = -0.759, 95% CI (-1.349, -0.168), p = 0.012]. Meta-regression and subgroup analysis results suggested that KD supplementation at a ratio of 4:1 was associated with remarkable prolongation of survival time in animals with limited tumor types. Conclusion: In summary, the preclinical evidence pointed toward an overall anti-tumor effect of the KD in animals studies currently available with limited tumor types.